KONTRIBUSI GURU PENGGERAK DALAM MENINGKATKAN KUALITAS SEKOLAH PENGGERAK STUDI KASUS DI SMAN 2 BANDAR LAMPUNG - Nelma Elpayuni; Triyuli Lestari; Eti Hadiati; Junaidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe the contribution of the driving teacher in improving the quality of the driving school at SMAN 2 Bandar Lampung. The approach used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The research focus includes the role of the driving teacher in internal training, supervision between teachers, and the development of learning modules that support the implementation of the Merdeka Curriculum. The results of the study show that the driving teacher plays an active role in improving the professional competence of teachers through internal training, strengthening collaboration and the quality of learning through supervision between teachers, and contributing to the development of an innovative curriculum. These contributions have a positive impact on improving the quality of learning, school management, and a more productive school culture. This research provides an empirical picture that can be used as material for evaluating and developing the mobilising teacher program in the future, as well as helping policy makers in optimising the role of mobilising teachers as agents of change in mobilising schools.